Salivary cortisol response to psychosocial stress in the late evening depends on CRHR1 genotype. (June 2020) - Weeger, J.; Ising, M.; Müller-Myhsok, B.; Uhr, M.; Schmidt, U.; Steiger, A.
Highlights: Variants of CRHR1 rs110402 reveal different cortisol response after psychosocial stress. Rare homozygous T carrier of CRHR1 rs110402 have significant higher cortisol levels after Trier Social Stress Test compared to common C carrier. Cortisone levels revealed no significant difference for variants of CRHR1 after psychosocial stress. Subjective perceived stress is higher in CC carrier of CRHR1 rs110402 compared to TT carrier. Abstract: The activation of the hypothalamus-pituitary-adrenal (HPA) axis is induced by stress. Imbalances in this system increase the risk of developing stress related disorders including mental illness. Variants in the single nucleotide polymorphism (SNP) rs110402 of the corticotropin-releasing hormone receptor type I ( CRHR1 ) gene have been shown in interaction with childhood maltreatment to increase the vulnerability to develop depressive symptoms in adulthood. In this study, the direct contribution of polymorphism of the CRHR1 gene (rs110402) to the salivary cortisol response to stress independently from childhood adversity was investigated. Healthy young men between the ages of 18 and 30, free from childhood maltreatment and early trauma, were genotyped (n = 121). To increase the power of the genetic analysis, only homozygous carriers of the common C (n = 31) and of the rare T (n = 21) allele were selected for this study and exposed to a Trier Social Stress Test (TSST) in the late evening (22.30 to 22.40). Salivary samples for the assessment of cortisol and its inactive metabolite cortisone were taken early in the evening (20.00), just before (22.30) and immediately after (22.40) as well as 15 minutes after stress exposure (22.55). Participants with the TT genotype showed higher cortisol levels 15 minutes post stress compared to participants with the CC genotype. No genotype differences were found for cortisone. Interestingly, TT participants reported lower subjective perceived stress levels before the TSST, but not after stress exposure. These results confirm that variants of rs110402 in the CRHR1 gene contribute to an increased stress response. Contrary to previous findings, however, this effect could be observed in subjects reporting no exposure to childhood maltreatment or early trauma.